Application of Filter Cake on Growth of Upland Sugarcanes - Purwono, ,; Sopandie, Didy; Harjadi, Sri Setyati; Mulyanto, Budi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2011)
Recently planting site of sugarcane was shifted from lowland to upland area. Sugar cane cultivation in upland has many constraints, especially limited water supply and low nutrition availability. The objectives of this research were to study the influence of application of composted filter cake on growth and water use efficiency of upland sugar cane. The research was conducted in Jengkol, Kediri. Treatments consist of three factors: frequency of irrigation (once every 1 week, once every 2 weeks, and once every 3 weeks); sugarcane varieties (PS-862 and PS-864); and compost doses (0, 2.5, 5, and 7.5 ton ha-1). Split plot design with three replications was used in each irrigation treatment, using composted filter cake as main plots and sugarcane varieties as sub plots. The results showed that the highest sugar content was reached at application of 5 ton ha-1 compost and the greatest crystal sugar was reached at 3.09 ton ha-1 compost. Compost application at 5 ton ha-1 on each planted row can reduce frequency of irrigation from once a week to once every 2 weeks.